2022
DOI: 10.1172/jci.insight.154250
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblastic reticular cells mitigate acute GvHD via MHCII-dependent maintenance of regulatory T cells

Abstract: Acute graft-versus-host disease (aGvHD) is a life-threatening complication of allogeneic hematopoietic cell transplantation (allo-HCT) inflicted by alloreactive T cells primed in secondary lymphoid organs (SLOs) and subsequent damage to aGvHD target tissues. In recent years, regulatory T cell (Treg) transfer and/or expansion has emerged as a promising therapy to modulate aGvHD. However, cellular niches essential for fostering Tregs to prevent aGvHD have not been explored, yet. Here, we tested whether and to wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…The finding that FRCs in murine LNs express and display antigenic peptides derived from peripheral tissue antigens ( Fletcher et al, 2010 ) suggests that direct antigen presentation by FRCs affects T cell responses. Indeed, a recent study using genetic ablation of the MHCII molecule in Ccl19-Cre + cells revealed that FRCs shape CD4 + T cells’ responses in a murine model of acute graft-versus-host disease (GVHD) with reduced expansion of FoxP3-expressing CD4 + T cells and invariant natural killer (NK) T cells ( Shaikh et al, 2022 ). Likewise, ECM components provided by FRCs have been shown to alter the effector–regulatory T cell ratio with increased allograft reactivity in mice lacking laminin α4 expression on Pdgfrb-Cre + cells ( Li et al, 2022 ).…”
Section: Conserved Frc Niche Functions Across Lymphoid Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that FRCs in murine LNs express and display antigenic peptides derived from peripheral tissue antigens ( Fletcher et al, 2010 ) suggests that direct antigen presentation by FRCs affects T cell responses. Indeed, a recent study using genetic ablation of the MHCII molecule in Ccl19-Cre + cells revealed that FRCs shape CD4 + T cells’ responses in a murine model of acute graft-versus-host disease (GVHD) with reduced expansion of FoxP3-expressing CD4 + T cells and invariant natural killer (NK) T cells ( Shaikh et al, 2022 ). Likewise, ECM components provided by FRCs have been shown to alter the effector–regulatory T cell ratio with increased allograft reactivity in mice lacking laminin α4 expression on Pdgfrb-Cre + cells ( Li et al, 2022 ).…”
Section: Conserved Frc Niche Functions Across Lymphoid Organsmentioning
confidence: 99%
“…Additionally, early blockade of Notch, within the first 48 h following transfer, permits the expansion of donor FoxP3 + regulatory T cells ( Chung et al, 2017 ). The ability of donor T cells to recognize allo-MHC-peptide complexes presented by Ccl19-Cre + FRCs appears to further license the expansion of regulatory T cells and attenuate the severity of GVHD ( Shaikh et al, 2022 ). Moreover, CD25-mediated IL-2 trans-presentation by LN FRCs attenuates Th17 cell differentiation resulting in dampened tissue pathology in Th17-mediated autoimmune disorders such as experimental autoimmune encephalomyelitis, experimental psoriasis, and antigen-induced arthritis ( Kim et al, 2022 ).…”
Section: Frc–immune Cell Interactions In Inflammatory Diseases and Ca...mentioning
confidence: 99%
“…In vitro and in vivo evidence indicates that FRCs possess the capacity to inhibit the expansion of effector T cells during an immune response . In murine models of graft versus host disease (GVHD), FRCs have been found as hubs for the proliferation of Tregs, , and de novo conversion of conventional T cells to Tregs. ,,, Acute GVHD damages the FRC network and reduces the presentation of PTAs, which is essential for deleting autoreactive T cells . In rodents, repetitive allograft transplantations drove FRCs to deposit excessive collagens, resulting in an altered lymph node microarchitecture coinciding with decreased Tregs and graft rejection.…”
Section: Introductionmentioning
confidence: 99%